"Contested policy mobility": the creative transformation and temporary use of brownfields in Redtory, Guangzhou. Issue 6 (3rd July 2017) - Liu, Xuan
ABSTRACT: This article argues that the changing distribution of power between coalitions of stakeholders challenges typical top-down dynamics of policy mobility, and causes contestations that in turn lead to the multi-scalar co-construction of policy- and place-making in China. When property-led redevelopment, commandeered by the coalition between government and investors, could no longer dominate the renewal of brownfield sites, a nationally endorsed mobile policy of creative transformation led China's renewal of these areas into a new phase of "contested policy mobility". Three kinds of contestations have been observed in Redtory, Guangzhou. First, in adopting the alternative mobile policy of using brownfields temporarily before permanent redevelopment, local governments were aiming to retain control of development rights throughout a nationally mandated urban economic "creative transformation" process. Second, emerging new interest groups from within the public sphere were able to resist subsequent redevelopment plans, thereby challenging the mobile policy's top-down momentum. Finally, divisive interests within the coalition ultimately weakened their power when contesting the government and investors.